Analisis Peran Kepemimpinan Transformasional Dalam Meningkatkan Kinerja Tim Para Guru Di Tk It Azkiyatun Najah - Nadya amalia rizky panjaitan; Putri Maydani Harahap; Sikni Sari Siagian; Zuriatun Fitrah; Rizki Akmalia (Journal of Management and Creative Business, 2024)
This research discusses the role of transformational leadership in improving the performance of the teacher team at TK IT AZKIYATUN NAJAH. This study aims to identify important elements that influence team performance and develop effective strategies for improving performance. Qualitative research methods were used with selected interviews and related data collection. The research results show that transformational leadership has a positive impact on team performance. Transformational leadership is characterized by a clear vision, vision management, and team motivation. A positive relationship between transformational leadership and team performance was found, with leaders able to motivate, build trust, and strengthen team engagement. Supporting factors and strategies for implementing transformational leadership are also discussed. The implications of this research are expected to provide better insight into how transformational leadership can improve team performance in the educational context of TK IT AZKIYATUN NAJAH.